Estudo químico das flores de Hortia oreadica (Rutaceae) - Zequin, Marina Cristina (Universidade Federal de São Carlos, 2018)
The present work describes the analysis of apolar and polar extracts from flowers of Hortia oreadica, a species of the family Rutaceae. Since these flowers had not been widely studied, and due to the chemosystematic value of this species in the taxonomy of the genus Hortia, it was decided to carry out this study in order to isolate secondary metabolites that would aid in a better classification of the genus. The extracts were analyzed by GC-MS, HPLC-DAD and 1H NMR; after isolated, the compounds were analyzed by 1D and 2D NMR (1H, 13C, COSY, HMBC, HSQC) in order to elucidate the chemical structures. Six major compounds were identified by GC-MS in the hexane extract (EH) of the flowers: trans-muurola-4-(4), 5-diene, cuparene, β-bisabolene, (Z) -holidolol, 1H-cycloprop(e) azulen-7-ol and guaiol. From the E.H., two triterpenes were identified: 3α-hydroxytirucalla-7,24-dien-21-oic acid and tirucalla-7,24-dien-3β-ol, being these unpublished in the genus Hortia. From the methanolic extract (E.M.) it was possible to isolate and identify the flavonoid: quercetin-3-β-D-glucoside, and from the ethyl acetate extract (E.A.) it was possible to isolate six limonoids, still in the elucidation process. From this study it was possible to observe the existence of precursors and limonoids in H. oreadica flowers, an outcome that had not yet been reported in the literature.
Chemical study of the flowers of Hortia oreadica (Rutaceae)
Keywords: Hortia oreadica; Rutaceae; CIENCIAS EXATAS E DA TERRA::QUIMICA